Advances in Fractional-Order Neural Networks, Volume II - Ivanka Stamova; Gani Stamov; Xiaodi Li (Fractal and Fractional, 2023)
Fractional-order neural network models have become an active research subject and have attracted increasing attention in many fields [...]